An assessment of the effectiveness of water management in South Africa - Candice Barnard; Justin Shuttleworth; Mark C. Verwoerd (African Journal of Environmental Economics and Management, 2018)
In South Africa, there are many challenges regarding water management. Inadequate rainfall, may contribute to mismanagement, hence political breakdowns and racial groups do also contribute to the problem. To list some of the major challenges for effective management are: limited physical resources, a long cycle of inadequate rainfall, a rapid growing population, and stagnant economies. Water resource management is crucial for human security. In South Africa, almost everyone is affected by mismanagement of water resource, hence those living in poor area are the most affected as they do not have access to potable water and proper sanitation. Many policy-makers, researchers, and water managers advocate that water must be managed at the level of river basins, based on the argument that river basins are a ‘‘natural’’ unit and thus the logical unit for water management. Although stakeholder participation in water management is advocated, actually including the poor and achieving substantive stakeholder representation has proven elusive in practice. More often than not, participation is little more than token consultation, with no decision-making power in the hands of the people concerned? Too often, the participation discourse draws attention away from the very real social and economic differences between people and the need for the redistribution of resources, entitlements, and opportunities. This is typified by the definition of stakeholders as water.